2014
DOI: 10.1103/physrevb.89.104401
|View full text |Cite
|
Sign up to set email alerts
|

Exchange interactions in Ca3Co2O6probed locally by NMR

Abstract: We have measured the nuclear spin-lattice relaxation of 59 Co in the geometrically frustrated Ising-type spin-chain system Ca 3 Co 2 O 6 as a function of temperature and applied magnetic field. In the nearly-saturated ferrimagnetic and ferromagnetic regimes considered here, the field-dependent energy scales governing the spin-lattice relaxation rates reflect the energy cost of a spin flip in the Co ions adjacent to the probed nuclei. This results in a thermally activated form for the nuclear relaxation rates, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…Due to J 2 and J 3 , the Fourier transform J(q) of exchange interactions has minima at incommensurate wavevectors ±q min with q min = (0, 0, 2π + ). The estimate for CCO is /(2π) ≈ −0.0061 for J 2 J 3 0.046|J 1 | suggested by NMR [37]. On one hand, because of this deviation, a commensurate three-sublattice ordered state (φ(r) ∼ const.)…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Due to J 2 and J 3 , the Fourier transform J(q) of exchange interactions has minima at incommensurate wavevectors ±q min with q min = (0, 0, 2π + ). The estimate for CCO is /(2π) ≈ −0.0061 for J 2 J 3 0.046|J 1 | suggested by NMR [37]. On one hand, because of this deviation, a commensurate three-sublattice ordered state (φ(r) ∼ const.)…”
mentioning
confidence: 92%
“…1). An ab initio study [36] suggested |J 1 | J 2 J 3 and an NMR experiment reported J 1 = −23.9(2) K and J 2 + J 3 = 2.3(2) K, suggesting J 2 = 1.1 K and J 3 = 1.2 K to explain the SDW ordering vector [37]. Below, for simplicity, we assume J 2 = J 3 .…”
mentioning
confidence: 99%
“…Though these oxides offer a vast field for the investigation of magnetism, only few of them have been investigated except for the two first "m=0, n=1" members. Indeed Ca3Co2O6, after the evidence for its particular magnetization steps behavior [6][7][8][9][10][11][12], has been later on investigated by many authors for the complex nature of its magnetism [13][14][15][16][17][18][19][20][21][22][23][24]. The other m=0, n=1 member, Ca3CoMnO6 was more recently studied for its particular magnetic order and its multiferroicity [25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…1) more than an order of magnitude weaker. 10,11,12 A combination of low dimensionality and geometric frustration on the triangular lattice leads to unexpectedly complex magnetic behavior of Ca3Co2O6, debated for a long time. 13,14,15,16,17,18,19 According to the latest results, below the Néel temperature TN = 25 K the incommensurate amplitude modulated spin density wave (SDW) magnetic state with a propagation vector qsdw = (0, 0, 1.01) is formed.…”
Section: Introductionmentioning
confidence: 99%
“…15 In the external fields several magnetization plateaus were detected in Ca3Co2O6, associated with the formation of ferri-and ferromagnetic states. 12,14,20 While novel magnetoelectric phenomena were observed in parent Ca3Co2O6, 21 its substituted compounds Ca3Co2-xMnxO6 (x ~ 1) are improper multiferroics with a notable ferroelectric polarization. 22 An appearance of competing magnetic states in Ca3Co2O6 results from a delicate balance of intra-and interchain magnetic interactions realized on the geometrically frustrated triangular lattice, which can be tuned by variation of external parameters like temperature and magnetic field.…”
Section: Introductionmentioning
confidence: 99%